Selection criteria of methods of disinfection and sterilization of endodontic instruments - N. A. Shalimova; A. V. Sevbitov; N. N. Filatov; E. V. Zolotova; M. Yu. Kuznetsova (Сеченовский вестник)
One of the most important ways of prevention nosocomial infections in outpatient dental practice is disinfection and sterilization of endodontic fi les. The present study evaluated the effect of various methods of disinfection and sterilization on the cutting efficiency of fi les. It was revealed that cutting efficiency of endodontic fi les decreases after all types of sterilization, mostly after sterilization with dry hot air, and at least — after the chemical sterilization. Because the force applied on profile increases after each cycle of sterilization, in this case the probability of fi le breakage increases, too.